KINERJA KANTOR PELAYANAN PAJAK PRATAMA (KPPP) MEULABOH DALAM MENINGKATKAN PELAYANAN MINAT WAJIB PAJAK - Alimas Jonsa; Yuni Salwan (Universitas Teuku Umar, 2017)
Primary Tax Office Meulaboh (KPPP) has an important role in improving the performance of public services in terms of extension function, service, and supervision to taxpayers. If seen from the function of the Primary Tax Office Meulaboh it is helpful to the Directorate General of taxes in awaken the importance of taxes to the public. The problem in this research is how the performance of Primary Tax Office Meulaboh in increasing interest taxpayers. The purpose of this study is to determine the performance of Primary Tax Office Meulaboh in increasing interest taxpayers. The research method used in this research is qualitative research method with descriptive approach. The source of data in this study consists of primary and secondary data. Then the technique of collected data used interview, observation and documentary. The location of this study was conducted in the Primary Tax Office Meulaboh West Aceh. Based on the results of research in the discussion KPPP Meulaboh in improving performance attract taxpayers. First, productivity KPPP Meulaboh not achieve results in accordance with the vision and mission of the grounds are still no customer complaints. Second, the quality of service KPPP Meulaboh also not yet maximal, the reason there are still many queues. Third; The responsiveness of KPPP Meulaboh is not good, the responsibility of KPPP Meulaboh still not maximal in giving the requirement for the taxpayer. Further Accountability KPPP Meulaboh give good results, because the responsibility is carried out according to the procedures of KPPP Meulaboh. Keywords: performance, Primary Tax Office Meulaboh, taxpayers